Atividade educativa da enfermeira: preparo e desempenho - Secaf, Victoria (1977)
Hospital and publie health n-urses have the responsability, besides other functions5 to develop teaching performance, pointed towards the patients, their families, the community members and the nursing staff . Didactics. applied to nursing enables the nurse for this special work. . The data of a study acomplished among former students of two nursing schools showed clearly their meaning about certain aspects of didactics and teaching performance. The conclusions established positively that the gráduates have performed formely more teaching activities about health and staff training than now. The difference was raised mainly among staff training and length of time> content, applicability and explanation form of the program. There are differences between the teaching performance of the graduates at former davs and the time ■of data gathering. The obtained results allow us to verify how necessary is the study of the programs of our nursing schools as well as the activities performed by the hospital and publie health nurses.